2002
DOI: 10.1097/00000539-200207000-00036
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Motor Blocking Potencies of Epidural Bupivacaine and Ropivacaine in Labor

Abstract: The results of this study demonstrate that epidural ropivacaine is less potent than epidural bupivacaine in producing motor blockade during labor. The motor block potency relation is similar to the sensory potency ratio for these two drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 8 publications
1
42
1
2
Order By: Relevance
“…10 We used fentanyl in a concentration of 2 μg/ml as it was used most commonly in previous studies. Motor block from local anaesthetic can be minimized either by reducing the concentration of the local anaesthetic or by choosing a local anaesthetic with a high differential sensory: motor block ratio, such as Ropivacaine 11 The advantage of using a low concentration of local anaesthetic was well demonstrated in Comparative Obstetric Mobile Epidural Trial (COMET). 12 This showed that the instrumental vaginal delivery rate was less frequent when a low dose epidural regimen (Bupivacaine 0.1% with Fentanyl 0.0002%) was compared with a traditional epidural regimen (Bupivacaine 0.25%).In the present study 10 ml of 0.125% of Ropivacaine and 10 ml of 0.125% Bupivacaine with 2 mcg/ml of fentanyl are used for initiation and then 6-8 ml of the study drugs are used for maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…10 We used fentanyl in a concentration of 2 μg/ml as it was used most commonly in previous studies. Motor block from local anaesthetic can be minimized either by reducing the concentration of the local anaesthetic or by choosing a local anaesthetic with a high differential sensory: motor block ratio, such as Ropivacaine 11 The advantage of using a low concentration of local anaesthetic was well demonstrated in Comparative Obstetric Mobile Epidural Trial (COMET). 12 This showed that the instrumental vaginal delivery rate was less frequent when a low dose epidural regimen (Bupivacaine 0.1% with Fentanyl 0.0002%) was compared with a traditional epidural regimen (Bupivacaine 0.25%).In the present study 10 ml of 0.125% of Ropivacaine and 10 ml of 0.125% Bupivacaine with 2 mcg/ml of fentanyl are used for initiation and then 6-8 ml of the study drugs are used for maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Data from epidural motor block and intrathecal analgesia studies have emerged the potency hierarchy as bupivacaine>levobupivacaine>ropivacaine. [2][3][4][5]16 In another study, adding sufentanil to 0.25% bupivacaine provided rapid onset of analgesia and prolonged the duration of analgesia, but the qual- Values were presented as n(%).…”
Section: Discussionmentioning
confidence: 99%
“…Sufentanil is the most potent opioid. [2][3][4][5][6][7] Bupivacaine and sufentanil are frequently used together. 1,[8][9][10] However, the lowest doses that produce effective analgesia is still controversial.…”
mentioning
confidence: 99%
“…However, it does not estimate the volumes of local anesthetics necessary to promote anesthesia in 95% and 99% of the patients, which would be clinically more relevant 23 . For this reason, Probit regression was used to calculate the estimated volumes of anesthetic effective in 95% and 99% of the patients 24 . Both methods use normal distribution to estimate the effective volumes.…”
Section: Discussionmentioning
confidence: 99%